Biblioteka w Zwierzynie:nowa przestrzeń, nowe możliwości = The Library in Zwierzyn: New Space, New Opportunities - Markiewicz, Sylwia (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The article "The Library in Zwierzyn: New Space, New Opportunities" analyzes the transformations that have occurred at the Municipal Public Library in Zwierzyn following its modernization and relocation to a new building in 2017. The author emphasizes that libraries must adapt to the changing needs of local communities. The new library space in Zwierzyn, inspired by Scandinavian architectural solutions, offers 390 m? of open, multifunctional space, allowing for the creation of zones for various user groups and the organization of diverse cultural and social events. In addition to lending books, the library hosts discussion book clubs, theatre classes for seniors, and provides services such as "books on the phone". The modernization of this institution, support from local authorities, and the engagement of the community and a three-member team of librarians have made it an important centre for cultural life in the Municipality of Zwierzyn. The increase in the number of users and numerous distinctions, such as high positions in Library Rankings, testify to the success of this investment. The article also highlights the challenges the library faces, including further adaptation to technological changes and the continuous adjustment of its offers to meet the needs of the local community.
Keywords: architektura i budownictwo; biblioteka (budynek); biblioteka publiczna; bibliotekarstwo; Gmina Zwierzyn; Gminna Biblioteka Publiczna w Zwierzynie; integracja społeczności; kultura lokalna; promocja czytelnictwa; architecture and construction; library (buidling); public library; librarianship; Municipality of Zwierzyn; Municipal Public Library in Zwierzyn; community integration; local culture; promotion of reading